Perbandingan Efektifitas Media Audio Visual Dan Modul Terhadap Peningkatan Pengetahuan Dan Keterampilan Mahasiswa S1 Keperawatan Dalam Melakukan Alih Baring - Nopriadi; Siti Nurhaliza; Yufitriana Amir (STIKes Payung Negeri Pekanbaru, 2021)
Nursing transfer is one of the competencies that nursing students must master. This competence can be achieved through a learning process with various media. The use of audio-visual media can make the delivery of information more real than module media. This study aims to determine the difference in the effectiveness of audio-visual media and modules on increasing the knowledge and skills of undergraduate nursing students in carrying out bed transfer. This study used a quantitative method with a quasy experimental design with pretest and posttest design with two comparison treatments. The research sample was 68 respondents who were taken simple randomly by drawing the respondent's name. The analysis used was univariate analysis and bivariate analysis using the T test. Results: There was an increase in the average knowledge of students after being given audio-visual learning of 7.73 and p value 0.000 (p <0.05) and in the module group of 6, 38 and p value 0.002 (p <0.05). There was an increase in the average score of knowledge which was higher in the audio visual group than in the module by 1.706 and a p value of 0.501. Meanwhile, for skills there was an increase in the average skills of students after being given learning through audio-visual of 10.29 and p value of 0.000 (p <0.05) and in the module group of 8.59 and p value of 0.000 (p <0.05). ). There was an increase in the average score of skills that was higher in the audio visual group than in the module of 1.853 and a p value of 0.021. Audio-visual media has a higher influence on students' knowledge and skills in carrying out bed transfer. Keywords: audio visual, module, bed transfer, instructional media